2011
DOI: 10.5301/jn.5000030
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2, endothelial dysfunction and renal involvement in patients with systemic lupus erythematosus

Abstract: Ang2 can reflect the extent of endothelial activation and may be used as a biomarker of both disease activity and renal involvement in SLE patients. Ang2 level cannot distinguish between proliferative and non proliferative lesions in LN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…This finding coincides with the results of other investigators [9,22] who found that Ang-2 level was upregulated in the glomeruli of patients with LN, and it has also significant positive correlation with proteinuria; therefore, the current study denotes that there is a close relation between circulating Ang-2 and vascular barrier function, presented by proteinuria as a marker for glomerular endothelial permeability. These findings are in line with increased glomerular expression of Ang-2 in the preclinical models of glomerulonephritis [39].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This finding coincides with the results of other investigators [9,22] who found that Ang-2 level was upregulated in the glomeruli of patients with LN, and it has also significant positive correlation with proteinuria; therefore, the current study denotes that there is a close relation between circulating Ang-2 and vascular barrier function, presented by proteinuria as a marker for glomerular endothelial permeability. These findings are in line with increased glomerular expression of Ang-2 in the preclinical models of glomerulonephritis [39].…”
Section: Discussionsupporting
confidence: 95%
“…Moreover the current work showed that, serum Ang-2 levels were significantly higher in patients with LN than in those without nephritis. This is in accordance with the results found by El-Banawy et al, [22] who found that Ang-2 was significantly elevated in SLE patients and closely correlated with renal involvement.…”
Section: Discussionsupporting
confidence: 94%
“…With respect to vascular traits, higher Ang-2 levels were associated with greater IMT in children on dialysis (n=24)9 and with low FMD in a study of 81 patients with systemic lupus erythematosus and controls 11. By contrast, Ang-2 levels were not associated with common carotid artery IMT in a combined sample of 97 patients with diabetes mellitus and 35 healthy controls10 and in 14 children with predialysis chronic kidney disease 9.…”
Section: Discussionmentioning
confidence: 97%
“…Due to its physiological properties, it is conceivable that Ang-2 and sTie-2 affect subclinical CVD traits. Indeed, higher Ang-2 levels have been associated with greater intima media thickness (IMT) in children on chronic dialysis9 and in adults,10 and with lower flow-mediated dilation (FMD) in patients with systemic lupus erythematosus and in controls 11. Additional evidence indicates that Ang-2 levels might also correlate with impaired cardiac function and heart failure disease stage 12 13.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have isolated factors in lupus serum that could induce endothelial cell dysfunction. Among these include oxidized LDL, type I interferons, pro-inflammatory HDL (4), toll-like receptor (TLR) 7 and 9 activation by RNA and DNA containing immune complexes (41), calprotectin (42) (a TLR4 agonist (43)), agiopoeitin-2 (44), Fc receptor activation from immune complexes (45), complement activation (4), anti-endothelial cell antibodies (4) and anti-phospholipid antibodies (46). Targeted interventions for these factors have yet to be proven to restore endothelial function in SLE patients.…”
Section: Discussionmentioning
confidence: 99%